Self-Construal Priming Modulates Self-Evaluation under Social Threat - Zhang, Tianyang; Xi, Sisi; Jin, Yan; Wu, Yanhong (Frontiers in Psychology, 2017)
Previous studies have shown that Westerners evaluate themselves in an especially flattering way when faced with a social-evaluative threat. The current study first investigated whether East Asians also have a similar pattern by recruiting Chinese participants and using social-evaluative threat manipulations in which participants perform self-evaluation tasks while adopting different social-evaluative feedbacks (Experiment 1). Then further examined whether the different response patterns can be modulated by different types of self-construal by using social-evaluative threat manipulations in conjunction with a self-construal priming task (Experiment 2). The results showed that, as opposed to Westerners’ pattern, Chinese participants rated themselves as having significantly greater above-average effect only when faced with the nonthreatening feedback but not the social-evaluative threat. More importantly, we found that self-construal modulated the self-evaluation under social-evaluative threat: following independent self-construal priming, participants tended to show a greater above-average effect when faced with a social-evaluative threat. However, this pattern in conjunction with a social threat disappeared after participants received interdependent self-construal priming or neutral priming. These findings suggest that the effects of social-evaluative threat on self-evaluation are not culturally universal and is strongly modulated by self-construal priming.